Higher Expression of DNA (de)methylation-Related Genes Reduces Adipogenicity in Dental Pulp Stem Cells - Argaez-Sosa, Adaylu A.; Rodas-Junco, Beatriz A.; Carrillo-Cocom, Leydi M.; Rojas-Herrera, Rafael A.; Coral-Sosa, Abel; Aguilar-Ayala, Fernando J.; Aguilar-Pérez, David; Nic-Can, Geovanny I. (Frontiers in Cell and Developmental Biology, 2022)
Obesity is a significant health concern that has reached alarming proportions worldwide. The overconsumption of high-energy foods may cause metabolic dysfunction and promote the generation of new adipocytes by contributing to several obesity-related diseases. Such concerns demand a deeper understanding of the origin of adipocytes if we want to develop new therapeutic approaches. Recent findings indicate that adipocyte development is facilitated by tight epigenetic reprogramming, which is required to activate the gene program to change the fate of mesenchymal stem cells (MSCs) into mature adipocytes. Like adipose tissue, different tissues are also potential sources of adipocyte-generating MSCs, so it is interesting to explore whether the epigenetic mechanisms of adipogenic differentiation vary from one depot to another. To investigate how DNA methylation (an epigenetic mark that plays an essential role in controlling transcription and cellular differentiation) contributes to adipogenic potential, dental pulp stem cells (DPSCs) and periodontal ligament stem cells (PLSCs) were analyzed during adipogenic differentiation in vitro. Here, we show that the capacity to differentiate from DPSCs or PLSCs to adipocytes may be associated with the expression pattern of DNA methylation-related genes acquired during the induction of the adipogenic program. Our study provides insights into the details of DNA methylation during the adipogenic determination of dental stem cells, which can be a starting point to identify the factors that affect the differentiation of these cells and provide new strategies to regulate differentiation and adipocyte expansion.